The influence of oral and written information on antiretroviraldrugs in the knowledge of users with HIV/AIDS - Anya Pimentel Gomes Fernandes Vieira; Regina Flávia de Castro Almeida (Universidade de Fortaleza, 2010)
Objective: To assess the influence of oral and written transmission of information on antiretroviral drugs in knowledge generation in their users and in the retention of information by them. Method: In the first phase, 18 individuals with HIV/AIDS treated at a referral hospital analyzed three brochures containing information on antiretroviral drugs and chose the best. In the second phase, three groups of 47 individuals with HIV/AIDS who received antiretroviral drugs in the same hospital were formed. The first group, considered the control group (group "C") received their medication at the pharmacy as usual, without any additional information; the second group (group "F") received a brochure with information about the drug in use, which should be read at that moment; and the third group (group "O") received orally, the same information detailed in the brochure. All answered a questionnaire that assessed their knowledge on the referred drug. Results: The responses of group "O" had a higher level of agreement with the information they received regarding action of the drug in the body (78.7%), duration of treatment (83%), procedure when missing a dose (91.5%) and storage (95.7%). Conclusion: The transmission of information, whether oral or written, generates knowledge and the instructions and information when orally transmitted, in a detailed manner and in appropriate language, are more easily understood and assimilated. It appears also that, in the studied group, oral information resulted more immediately effective than written one.